Pengaruh Kompetensi Kerja, Keterlibatan Kerja, dan Beban Kerja terhadap Kinerja Pegawai Bawaslu, Kabupaten Boyolali - Medya Wulandari; Hari Purwanto; Alean Kistiani Hegy Suryana (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This article examines how work competence, work involvement, and workload, both individually and jointly, shape employee performance at the Election Supervisory Body (Bawaslu) of Boyolali Regency. A causal-associative quantitative design was employed, covering the full population of 40 employees through a census (saturated sampling), consisting of permanent staff together with members of the Sub-district Election Supervisory Committee (Panwaslu Kecamatan). A five-point Likert questionnaire supplied the primary data, which were processed using multiple linear regression in SPSS. Before hypothesis testing, the research instrument was verified as valid and reliable, and the regression model passed the classical assumption checks for normality, multicollinearity, and heteroscedasticity. Findings show that each of the three predictors, work competence, work involvement, and workload, exerts a positive and significant partial influence on employee performance, with competence being the most influential of the three. Taken together, the variables significantly shape performance and account for 58.2 percent of its variance (Adjusted R² = 0.582). The study reinforces Human Capital Theory within a public-oversight setting marked by fluctuating workload, demonstrating that workload, when handled appropriately, can drive performance rather than undermine it. On a practical level, the findings point to the importance of structured competence-building, stronger engagement initiatives, and a more balanced workload distribution across Bawaslu Boyolali Regency to strengthen election-oversight performance.